Management of Technology in the Higher Education Sector in Aceh Adoption and Measurement during the Pandemic Covid-19 - Salam, Rudi; Rahmawati, Sri; Novita, Nanda; Satria , Habib; Rafi’i, Muhammad (Sinkron : jurnal dan penelitian teknik informatika, 2021)
Technology Management is used to adapt to changing environmental conditions and technological advances and to create current transformations. Based on dynamic capability theory, this paper considers technology management as capability and measures it through the technology adoption capability maturity model to investigate the relationship between technology management practice and performance. Findings from empirical studies confirm that technology management in particular technology adoption is an important source of competitive advantage and contributes to the success of an online learning process in a positive way. The learning model presented by the lecturer in learning each material with all students uses online without any face-to-face activities. At the level of success, the lecturer felt that the learning he had done during the last few days was mostly only around 45% - 50% of the total material that had been explained  The negative impact felt by students is the ineffectiveness of online learning methods because lecturers and students cannot discuss actively and are constrained by time constraints on several online learning applications. addition, students feel less free to ask lecturers about materials that are not understood because they are only limited by typing WhatsApp group conversations, the quota runs out, and the number of assignments given to students is the most noticeable obstacle.